2015
DOI: 10.1007/s11695-015-1699-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification Models: How Well do They Predict Adverse Outcomes in a Large Dutch Bariatric Cohort?

Abstract: The overall majority of the included risk models are unsuitable for risk prediction. Only one model with an emphasis on surgeon- and center-related factors instead of patient-related factors predicted adverse outcome correctly in our external validation cohort. These findings support the establishment of specialty centers and warn benchmark data institutions not to correct bariatric outcome data by any other patient-related factor than age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 48 publications
(29 reference statements)
2
12
0
Order By: Relevance
“…Although no association between beta-blockade and serious postoperative complications was detected in the present study, increasing age, lower BMI, and lower disposable income were all associated with increased risk for such adverse events. While age is a well-known risk factor for postoperative complications after bariatric surgery [3,[22][23][24], BMI has been reported to be a poor predictor [3,22]. However, previous studies have reported a tendency towards higher risk for patients with extreme BMI values, both low and high [3,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although no association between beta-blockade and serious postoperative complications was detected in the present study, increasing age, lower BMI, and lower disposable income were all associated with increased risk for such adverse events. While age is a well-known risk factor for postoperative complications after bariatric surgery [3,[22][23][24], BMI has been reported to be a poor predictor [3,22]. However, previous studies have reported a tendency towards higher risk for patients with extreme BMI values, both low and high [3,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…These models could also serve as the basis for case-mix comparisons between different centers. Some prediction models that are based on the linear regression of patient-specific data allow for relatively simple and interpretable inference; however, so far they have been proven inaccurate and thus cannot be used in clinical practice [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the external validity of the RCT could be evaluated. Even though patients in the RCT had a slightly lower prevalence of associated co‐morbidity than those in in the non‐RCT group, the RCT cohort reflects the population of individuals having bariatric surgery throughout Europe. The RCT was conducted in a register setting, offering the potential for quick enrolment of patients and broad generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%